Mecanismos de sinalização em plântulas de sorgo e trigo em resposta ao alumínio mediados por gás sulfídrico - Fernanda Gomes da Silva (2016)
Aluminum (Al3+) is one of the main factors that limit crop productivity in acid soils. For this reason, it is important to identify and know the mechanisms of resistance of Al3+. The overproduction of reactive oxygen species is one of the first responses of plants to Al3+ exposure. Also, hydrogen sulfide (H2S) has been recognized as a key signaling molecule during plant response to (a)biotic stresses. This study focused on the evaluation of signaling processes activated in contrasting sorghum (Sorghum bicolor) and wheat (Triticum aestivum) genotypes during the response to Al3+ stress. The effect of an H2S donor in the mitigation of damages caused by Al3+ was also investigated. Sorghum genotypes were exposed to Al3+ (0 to 80 µM) in 200 µM CaCl2 (pH 4.0), while wheat genotypes were treated with 75 µM Al3+ prepared in one tenth total strength nutrient solution (pH 4.0). The key responses of seedlings were observed 48 h post Al3+ exposure. Al3+ was toxic to the sensitive genotypes (ATF8B, sorghum e Anahuac, wheat) while the cytotoxic effects in tolerant seedlings (ATF10B, sorghum e BH1146, wheat) were quite mild. The endogenous levels of H2S in Al-tolerant sorghum roots (ATF10B) were higher than those of Al-sensitive ones (ATF8B). The Al3+ treatment stimulated the activities of superoxide dismutase (SOD), ascorbate peroxidase (APX) and catalase (CAT) in Al-sensitive sorghum roots without affecting the activity of such enzymes in the Al-tolerant genotype. The pre-treatment with an H2S donor for 24 h caused contrasting effects on the studied plant species. The roots from pre-treatment of Alsensitive sorghum with H2S rescued the SOD, APX and CAT activities to the levels of control plants, followed by Al3+ exposure. The exogenous H2S also attenuated the morphological alterations triggered by Al3+ in Al-sensitive sorghum roots. Wheat roots exhibited increased endogenous levels of H2S upon Al3+ treatment. The increase in H2S levels induced by Al in wheat was accompanied by stimulation in β-ciano-alanine synthase (CAS) and decrease of Lcysteine desulfhydrase (L-DES), enzymes involved in the biosynthesis of H2S. The Al3+ also inhibited the dehydrogenase activity and superoxide anion production in Al-sensitive seedlings and at less extent in the Al-tolerant genotype. Cell death events seem to have been enhanced in the epidermis of sensitive wheat roots, but not in tolerant roots after Al3+ exposure. Different from the results obtained for sorghum roots, the pre-treatment of wheat roots with an H2S donor intensified cell death processes, inhibited cell respiration and stimulated SOD, APX and CAT enzymes in both genotypes, independently of Al3+ exposure. The increase of endogenous H2S levels induced by Al3+ exposure, associated with the exogenously generated H2S boosted the deleterious effects of such gas on wheat roots. Overall, the results indicate that 50 µM H2S contributes to the sorghum response to Al3+ while, in contrast, become toxic to the wheat genotypes. The H2S effects with respect to the plant response to Al3+ vary according to the plant species and gas concentration in plant cells.